THE IMPACT OF DISTRIBUTION OF FUNDING AND THE AMOUNT OF THIRD PARTY FUNDS ON THE PERFORMANCE OF BANK BCA SYARIAH PERIOD 2014 – 2021 - Husna, Ovilia; Hariyanto, Sidiq; Nurhana, Inka Ayu; Cahyani, Nita; Prastiwi, Iin Emy (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
The main problem in this thesis is the relationship of third party funds and financing to profits at Bank BCA Syariah. The purpose of this study is to determine how big the relationship between third party funds and financing to the profits of Bank BCA Syariah.This study uses the profitability variable using the Return On Asset (ROA) measurement, and the independent variable is TPF (Third Party Funds).This study aims to determine whether the amount of financing and Third Party Funds has an effect on the Profit of Bank BCA Syariah. This research was conducted in 2014-2021. This research is a quantitative research with secondary data. Data analysis using multiple linear regression analysis,Simultan test (Test F), Partial Test (Test t), And Test Koefisiens determinasi. Which I got from the quarterly financial statements of Bank BCA Syariah in 2014-2021.. But first, use the classical assumption test to test the quality of the data, before it is processed by regression. From the results of this study, it was found that third party funds and financing had no significant effect on the Profit Bank of BCA Syariah.